(3GQJTGa GdVQH ef dSGf GdYQHs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s ((3YGeQ Hf GdMGL MSf GdGJjGj, GdeGdcj GdTGPdj GdCRgQj s)
(3ChdgG (B:s
(3HGH GdeaYhd dg(B: (3JVGaQJ GdfUhU Ydi TQW Cf jchf eUOQkG hRYe jhfS Cf bhekG ef GdYQH jbhdhf s
(3BNQgG (B:s
(3hGdae HGdeje eVGakG fMh bhdg(B: (3Y(B: (3jUHM XeBf haj GdHMQ ageg GSJYeGdg HGdhGh hGdCda hGdjGA YfO CHj Ydj s
(3fSNI KGdKIs
(3JJab aj BNQgG eY BNQ GdfSNI GdChdi HGNJdGa jSjQ LOkG aj GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3fbdgG GdfGSN ef fSNI efbhdI ef fSNI HNW GdeDdas
(3hebGHdI YdjgG heDQNI SfI (B741(3g````s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs